Ankaferd Blood Stopper for Controlling Gastrointestinal Bleeding due to Distinct Benign Lesions Refractory to Conventional Antihemorrhagic Measures. (2010) - Kurt, Mevlut; Onal, Ibrahim Koral; Akdogan, Meral; Kekilli, Murat; Arhan, Mehmet; Sayilir, Abdurrahim; Oztas, Erkin; Haznedaroglu, Ibrahim Celalettin
Abstract : OBJECTIVE: To assess the hemostatic efficacy of the Ankaferd Blood Stopper (ABS, Ankaferd Health Products Ltd, Turkey) hemostatic agent for controlling gastrointestinal bleeding associated with various benign lesions refractory to conventional antihemorrhagic measures. METHODS: The records of all patients who underwent upper and lower endoscopy procedures at the Turkiye Yuksek Ihtisas Teaching and Research Hospital (Ankara, Turkey) between April 2008 and June 2009 were reviewed. Patients in whom ABS was used as a primary or adjuvant hemostatic agent were included in the study. Rates of bleeding control and postprocedural complications were documented. RESULTS: Hemostasis with no immediate complications was achieved in all patients within seconds of endoscopic application of ABS. CONCLUSIONS: ABS may have a role as a primary treatment or as an adjuvant to conventional modalities used to control gastrointestinal bleeding. Prospective controlled studies are needed to help establish its efficacy and, perhaps, offer a comparison with conventional hemostatic interventions.